Microdomination : how to leverage social media and content marketing to build a mini-business empire around your personal brand - Young, Trevor (Milton, Qld. : Wiley, 2013)
Microdomination is based on the premise of building a strong personal brand around what gets you jazzed every day and then growing a sustainable business enterprise around it.The book paints a vivid picture of the possibilities that exist today for someone who has experience and expertise in - and importantly, a passion for - a particular subject, topic, or vocation.
Includes bibliographical references and index.
Keywords: Small business -- Management; Small business marketing; Social media -- Economic aspects; Internet marketing